THE EFFECT OF LIQUIDITY, LEVERAGE, PROFITABILITY ON TAX AGGRESSIVENESS: CASE STUDY ON MANUFACTURING COMPANIES SUB PROPERTY AND REAL ESTATE SUB-SECTOR IN BEI - Zaufani Putri Khairun; Jummaini; Ghazali Syamni; Nurlela (Journal of Accounting Research, Utility Finance and Digital Assets, 2025)
This study aims to examine the effect of liquidity, leverage, and profitability on tax aggressiveness in property and real estate companies listed on the Indonesia Stock Exchange for the 2019-2023 period. The data collection technique uses secondary data in the form of financial reports accessed from the official website www.idx.co.id and also from the website of each company. The data that has been collected is processed using eviews. The population used in this study are property and real estate companies listed on the Indonesia Stock Exchange during the 2019-2023 period. The sample selection technique used purposive sampling technique and obtained 17 companies for 5 years with a total sample data obtained was 85 sample data. The data analysis method used in this study is panel data regression analysis. The research results found that, liquidity and leverage have no effect on tax aggressiveness, and profitability has a negative effect on tax aggressiveness in property and real estate companies listed on the Indonesia Stock Exchange for the 2019-2023 period. This study uses panel data to test manufacturing companies in the property and real estate sub-sector. Further research can consider the influence of these variables and expand the scope of research to other industrial sectors. The results of this study not only provide new insights into the situation of financial management in companies, but can also be a basis for further refining and developing existing theories.